“Knowing this is of no benefit, but ignorance of this is harmless” - Shukri Seytumerov (Крымское историческое обозрение)
As Islam spread, ties with non-Muslim communities expanded. Among those who converted to Islam were also scholars who know the Torah and the Gospel. Converting to Islam, they shared with Muslims biblical descriptions of events mentioned in the Qur`an and Sunnah. One of the biblical stories, mentioned in Quran and in commentaries to it, is well-known story about “people in cave” – seven sleeping lads. The legend is expounded in sura Al-Kahf. Worship of sleeping lads, that took place in the whole Christian world over time found reflection in Islamic tradition. This story acquired with popularity in the most remote parts of muslim territory. This process did not bypass the Muslims of the Crimea, expressed, for example, in the practice of turning to the legend about the inhabitants of the cave.